Influence of Steam Curing Method on the Performance of Concrete Containing a Large Portion of Mineral Admixtures. (24th April 2017) - Li, Mengyuan; Wang, Qiang; Yang, Jun
Abstract : A comparison was made between the impact of raising the thermostatic temperature and the impact of prolonging the thermostatic time on the performance of steam-cured concrete containing a large portion of fly ash (FA) or ground granulated blast furnace slag (GGBS) by analysing the form removal strength, chemically combined water content, reaction degree, strength development, chloride permeability, and volume stability. For the materials and test conditions reported in this study, raising the thermostatic temperature is more favourable for concrete containing FA, as indicated by the significantly higher form removal strength and the higher growth of reaction degree of FA compared with prolonging the thermostatic time. With an increase in the thermostatic temperature, the hydration degree of a binder containing FA or GGBS initially increases and subsequently decreases. Although concrete containing FA can obtain satisfactory form removal strength with steam curing at 80°C, the late strength development of concrete containing FA is slow for the same curing conditions. The effect of the late performance of resistance to chloride ion permeability improved by FA is better than the effect improved by GGBS. The risk of destroying the structure of concrete containing a large portion of FA or GGBS due to delayed ettringite formation (DEF) is minimal when specimens were steam-cured at 80°C.